THE IMPACT OF THE DIFFERENCE IN OIL VISCOSITY OF OILS ON THEIR MIXING DURING SEQUENTIAL PUMPING IN THE PIPELINES - Якимів, Йосип Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
There has been made the analysis of an impact of difference in oil viscosity on the volume of the mixture that is formed during their sequential pipage. The calculations are made for a real pipeline system for different combinations of pump inclusion in stations for a wide range of variation of oil viscosity. There has been worked out an algorithm for determining the throughput capacity of oil-trunk pipelines at different oil viscosities used for calculation the volume of the mixture. It is proved that the volume of the mixture increases when the difference of oil viscosity increases. Intensive growth of the mixture volume occurs at low viscosity values.